Factors influencing employee’s work motivation / Nur’Atiqah Daud - Daud, Nur’Atiqah (2014)
Every organization has their goals and achieving the goals need high commitment from the employees. Organization’s success is depending on employees work motivation. In the era of globalization, organization is highly competitive and having de-motivated employees are the major problem. Having motivated employees is important to any organization. A motivated employee means employee that highly productive in giving commitment to the work and this employee also will help organization achieve organization’s goals. According to Andrew (2004), commitment of all employees is based on rewards and recognition. It is important to show that management appreciated all of the effort by the employee. By this, employee will be more motivated to perform the next job and indirectly increasing organizational performance. Employee’s work motivation is the terminology used to describe whether employees were satisfied and contented their needs in the work place. Motivations for working are different among people. People are working because they can obtain something benefits from the work. These will impact morale and motivation as well as quality of work. Management of the company should need to understand what motivates his employees. What would encourage them that can contributes to high work performance yet not every employee will be motivated by the same thing. Management can include rewards and recognition, all the monetary incentives, building programs that can support work life balance. Management can make program such “Employee of the Month” to spotlighting employee whose achieve standard work performance. This will make employees feel they are part of the organization because their contributions were appreciated by the organization. Employees want to shows they are good in the job and they seek face-to-face feedback from their managers. Managers should give constructive criticism and help them perform their job more effectively and efficiently. Employees also want to feel that they are being heard with their opinions. This will make them feel that their opinions act a role in organization’s success. This is management’s job to inspire their employees in having high motivation while working. Employee’s work motivation is very vital in organization and it cannot be down-played. Motivated employees can increase organization’s productivity as well as improves overall performance. The current study on employee’s work motivation helps to know as much about the most influential factor which affects employee’s work motivation in D’Harmoni Telco Infra Sdn Bhd. This will help the management to provide suitable ways in order to motivate the employees. In this study it includes three factors which influencing employee’s work motivation such salary, rewards and recognition as well as leadership behavior.